Experimental Assessment of Ground Thermal Properties for Shallow Geothermal Energy - Irshidat, Mahmoud; Qaiymah, Sufian; Al-Bodour, Wassel (Salehan Institute of Higher Education, 2025)
Geothermal energy, being clean and renewable on both large and small scales, has become a field of interest for researchers in several areas such as cooling-heating systems, geothermal piles, and geothermal electricity. The purpose of this study is to explore the ground thermal behavior and relevant thermal soil properties for key regions in Jordan. These regions represent either major cities or areas with optimal seasonal temperature variations suitable for such applications. Three key locations were investigated: Tabarbour-Amman, Shafa-Badran-Amman, and Mafraq. Geotechnical soil investigations were conducted using hollow stem auger drilling, with soil samples collected at each meter of depth. Each sample was tested in the laboratory for thermal diffusivity, heat capacity, specific heat, and thermal conductivity. Additionally, thermocouples were installed in each borehole, and the holes were backfilled with the soil cuttings produced during drilling. Seasonal temperature profiles were developed for each site based on the measurements from the thermocouples. Temperature variations were also analyzed using the measured thermal soil properties within a mathematical heat transfer model, with results showing good agreement with the recorded measurements. Thermal diffusivity ranged from 0.315 to 0.365 mm²/s near the ground surface, and from 0.135 to 0.257 mm²/s at a depth of six meters. Thermal conductivity ranged from 0.197 to 0.351 W/m·K near the surface to 0.468 to 0.875 W/m·K at six meters depth. Ground temperature varied from a maximum during the hot season at the surface to a minimum during the cold season at six meters depth. The extreme temperature difference (4.4 to 5.25 °C), along with the observed values of diffusivity and heat capacity, indicates significant potential for energy extraction in the form of heat, in a cost-effective and time-efficient manner.